2013
DOI: 10.4161/auto.23959
|View full text |Cite
|
Sign up to set email alerts
|

Viroporin-mediated calcium-activated autophagy

Abstract: hijacked through viroporinactivated calcium/calmodulin-dependent kinase kinase-β signaling is required for rotavirus replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 0 publications
4
47
0
1
Order By: Relevance
“…Further study found that NSP4 activates the release of calcium from the ER into the cytoplasm, inducing calcium/calmodulindependent kinase kinase-β (CaMKK-β) signaling to trigger autophagy ( Fig. 5.3) [28,29]. Besides CaMKK-β signaling, a mutually complementary mechanism about a new small RNA was found in RV-initiated autophagy.…”
Section: Dsrna Virusesmentioning
confidence: 97%
“…Further study found that NSP4 activates the release of calcium from the ER into the cytoplasm, inducing calcium/calmodulindependent kinase kinase-β (CaMKK-β) signaling to trigger autophagy ( Fig. 5.3) [28,29]. Besides CaMKK-β signaling, a mutually complementary mechanism about a new small RNA was found in RV-initiated autophagy.…”
Section: Dsrna Virusesmentioning
confidence: 97%
“…CaM was originally identified in snake venom as an activator of cyclic nucleotide phosphodiesterase (PDE) [57] and subsequently shown to require [59] and bind Ca 2+ [60]. Shortly thereafter, the protein was independently “discovered” by several investigators working on different biological systems and given different names.…”
Section: A Key Ca2+/cam-dependent Kinase Cascade Emergesmentioning
confidence: 99%
“…Determining the subcellular localization of the active versus inactive forms of this kinase, in basal versus stimulated states, will shed light on unappreciated functions of CaMKK2. Various studies implicate CaMKK2 activity with phagocytosis [37], secretion [52], and autophagy [57], which involve trafficking of membrane-associated and soluble proteins. Whether CaMKK2 is tethered to any intracellular membranes and what mechanisms are in place to regulate its trafficking within the cell are important questions that warrant further investigation.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…ER is closely associated with autophagy, since ER is proposed to be the potential membrane source of autophagosomes, 14 and provides calcium signaling for autophagy induction. 15,16 Moreover, a variety of studies indicates that autophagy compensates for disposal of accumulated proteins result from ER stress, [17][18][19] suggesting that ER stress may be a trigger for autophagy induction. In the context of cerebral ischemia, the role of autophagy is under debate.…”
Section: Introductionmentioning
confidence: 99%